Role of inflammation and inflammasome activation in human bile cast nephropathy. Issue 6 (7th February 2020) - Giuliani, Kurt T. K.; Kassianos, Andrew J.; Kildey, Katrina; Grivei, Anca; Wang, Xiangju; Ungerer, Jacobus; Francis, Leo; Healy, Helen; Gois, Pedro F. H.
Abstract: Bile cast nephropathy (BCN) is an underdiagnosed cause of acute kidney injury (AKI). The precise pathogenesis of bilirubin tubular toxicity remains unknown. The aim of this study is to explore the cellular and molecular pathophysiology of human BCN. Paraffin‐embedded sections of renal biopsy tissue from a BCN patient were stained by immunohistochemistry (IHC) for oxidative stress (4‐hydroxynonenal), immune cell subpopulations, including dendritic cells (CD1c), macrophages (CD68) and T cells (CD3), and inflammasome activation by staining for active‐caspase‐1 and the inflammasome adaptor protein, ASC (apoptosis‐associated speck‐like protein containing a caspase activation and recruitment domain). Quantitative analyses of IHC staining were compared to healthy renal cortical tissue. We identified yellow to brown granular casts within the BCN case, consistent with the presence of bile pigment. The presence of bile pigment was associated with strong tubular 4‐hydroxynonenal staining intensity, a marker of oxidative stress. Diffuse tubulointerstitial inflammatory cell infiltrate was detected, with elevated CD1c, CD68 and CD3 staining. Foci of inflammasome activity were co‐localized with this intense immune cell infiltration, with increased active‐caspase‐1 and ASC staining. Our findings are the first to suggest that bile casts may lead to oxidative stress and trigger the inflammasome signalling cascade, leading to interstitial inflammation and driving AKI pathobiology. SUMMARY AT A GLANCE The report suggests that bile casts may lead to oxidative stress and trigger the inflammasome signalling cascade, leading to interstitial inflammation and driving bile cast nephropathy pathobiology. SUMMARY AT A GLANCE: The report suggests that bile casts may lead to oxidative stress and trigger the inflammasome signalling cascade, leading to interstitial inflammation and driving bile cast nephropathy pathobiology.